VD_FINDINFO HC / 2015 / 458 vom 11. Mai 2015 - VD Tribunal cantonal (2015)
OBLIGATION D'ENTRETIEN, ENFANT, MAJORITÉ{ÂGE}, FORMATION PROFESSIONNELLE | 277 al. 2 CC, 261 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH)